Phage therapy for environmental biotechnology applications - Singh, Suniti; Samson, Rachel; Hassard, Francis (Frontiers in Microbiology, 2025)
Environmental compartments, from soils and crop rhizospheres, to bio-reactors and municipal water networks have emerged as dynamic hot-spots for antimicrobial-resistance evolution and dissemination. Bacteriophages offer a precision, self-amplifying alternative to conventional biocides, yet their environmental deployment, intellectual-property space and commercial readiness remain only partially charted. Here, we critically synthesize the past decade of progress in phage-based interventions across three sectors: (i) soil remediation and crop-protection interfaces, where multi-phage cocktails suppress wilt- and blight-causing pathogens while preserving beneficial microbiota; (ii) biofuel and petro-energy infrastructures, in which lytic phages mitigate the microbiologically influenced corrosion and contaminated fermentations, restoring ethanol yields; and (iii) natural and engineered water systems, where phages show promise in treating recalcitrant biofilms, algal blooms and selectively ablate World Health Organization-priority pathogens. Meta-analysis of the World Intellectual Property Organization database reveals rapidly rising but geographically skewed patent activity, with China and the United States accounting for >61% of reviewed filings, and a gap between laboratory proof-of-concepts and marketed products. We identify bottlenecks, including lack of good manufacturing practice at scale, fragmented regulatory frameworks, and the evolutionary balance between single-phage precision and cocktail breadth. A roadmap is suggested that couples high-throughput phage discovery, synthetic tailoring and adaptive approval pathways. Together, these advances position environmental phage therapy to become a cornerstone of the One-Health response to increasing levels of microbial resistance.